Peran Bank Indonesia Dalam Pengawasan Keamanan Siber di Era Digitalisasi Perbankan - Rosita, Dita Puspa; Hidayah, Nur; Imon, Syarah Adilla; S, Suwarsit (Media Hukum Indonesia (MHI), 2024)
Rapid advances in digital technology have brought significant changes to the banking sector in Indonesia, increasing efficiency and expanding access to financial services. However, digitalization also presents new challenges, especially related to cyber security threats. The cyber attack case that hit Bank Syariah Indonesia (BSI) in 2023 revealed weaknesses in the security system which caused disruption to services and leakage of customer data. In this context, Bank Indonesia (BI) has an important role as a regulator that sets rules and standards to maintain the security of the financial system. This research adopts a literature study and policy analysis approach to assess the steps taken by BI in managing cyber security and responding to incidents that occurred at BSI. Research findings show that BI has designed a comprehensive cyber security policy, implemented strict supervision, and increased cooperation with various related parties. Apart from that, efforts to educate the public regarding the safe use of information technology are also a top priority. Overall, the success of banking digitalization relies heavily on the integration of technology with solid security policies to maintain public trust.